State synchronization of a class of homogeneous linear multi-agent systems in the presence of unknown input delays via static protocols. (May 2019) - Zhang, Meirong; Saberi, Ali; Stoorvogel, Anton A.; Liu, Zhenwei
Abstract: This paper studies state synchronization of homogeneous multi-agent systems (MAS) in the presence of unknown input delay via static protocols. The agents are coupled though part of their state. Both uniform input delay and nonuniform input delay are considered. We investigate two classes of agents, for which static linear protocol can be designed: squared-down passive and squared-down passifiable via input feedforward. A low-gain static protocol is designed for each of the two classes of agents such that state synchronization is achieved among agents with uniform or nonuniform input delay.